2000
DOI: 10.1074/jbc.275.17.12430
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state Kinetic Characterization and Crystallization of a Polychlorinated Biphenyl-transforming Dioxygenase

Abstract: The oxygenase component of biphenyl dioxygenase (BPDO) from Comamonas testosteroni B-356 dihydroxylates biphenyl and some polychlorinated biphenyls (PCBs), thereby initiating their degradation. Overexpressed, anaerobically purified BPDO had a specific activity of 4.9 units/mg, and its oxygenase component appeared to contain a full complement of Fe 2 S 2 center and catalytic iron. Oxygenase crystals in space group R3 were obtained under anaerobic conditions using polyethylene glycol as the precipitant. X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 43 publications
6
79
0
1
Order By: Relevance
“…3). These spectra are similar to those of the oxygenases of other ring-hydroxylating dioxygenases (17,29). The extinction coefficient of ISP TADO was 83.4 mM Ϫ1 cm Ϫ1 at 323 nm (25 mM HEPES, pH 7.3; 25°C) based on its sulfur content.…”
Section: Construction Of Expression Systemssupporting
confidence: 48%
See 1 more Smart Citation
“…3). These spectra are similar to those of the oxygenases of other ring-hydroxylating dioxygenases (17,29). The extinction coefficient of ISP TADO was 83.4 mM Ϫ1 cm Ϫ1 at 323 nm (25 mM HEPES, pH 7.3; 25°C) based on its sulfur content.…”
Section: Construction Of Expression Systemssupporting
confidence: 48%
“…Production of TADO components in suitably engineered pseudomonad strains greatly increased the amount of expressed, soluble protein, as was observed for biphenyl dioxygenase (BPDO [29]). Thus, the yield of ca.…”
Section: Discussionmentioning
confidence: 99%
“…Bedard et al (26) have previously reported the fact that the more recalcitrant PCB congeners are degraded more efficiently when present at very low concentration. There is no clear explanation for this observation; however, substrate inhibition of BPDO reaction caused by uncoupling of NADH oxidation to substrate oxidation has been demonstrated for several chlorobiphenyls (27). Nevertheless, clearly, variant p4 has acquired the capacity to oxygenate this co-planar congener.…”
Section: Metabolism Of Other Pcb Congeners By Variant P4 Bpdo-mentioning
confidence: 69%
“…The ferredoxin and ferredoxin reductase act as a short electron transport system from NADH to reduce the terminal dioxygenase (Broadus and Haddock, 1998). BphA1 and BphA2 are associated as an a3b3 heterohexamer Hirose et al, 1994b;Imbeault et al, 2000). BphA1 contains the motif Cys-X-His-X17-Cys-X2-His that forms a Rieske-type [2Fe-2S] cluster.…”
Section: Enzymes Involved In Pcb Degradationmentioning
confidence: 99%
“…An analysis of the substrate specificity pattern of these chimeras toward selected PCB congeners indicate that the catalytic capacity of hybrid enzymes comprised of an a and a b subunit recruited from distinct BP Dox is not determined specifically by either of the two subunits. Imbeault et al (2000), crystallized an oxygenase component of BP Dox of Comamonas testosteroni B-356 and got preliminary x-ray differentiation data.…”
Section: Enzymes Involved In Pcb Degradationmentioning
confidence: 99%